Penyelesaian Sengketa Wanprestasi Secara Alternatif Melewati Badan Arbitrase Nasional Indonesia (BANI) - Dewi Ratrika Rinupa Sejati (Indonesian Journal of Law and Justice, 2024)
Peaceful resolution of disputes is the main goal in the modern legal system. One form of peaceful resolution, namely arbitration, is recognized as an effective way to resolve disputes firmly and bindingly. Arbitration is part of Alternative Dispute Resolution (ADR), which includes various methods of resolution outside of court or litigation. In the context of resolving default disputes, the Indonesian National Arbitration Board (BANI) is an efficient option. This research aims to analyze the role and benefits of arbitration in handling default disputes, especially those related to BANI. The research method used is normative legal research by collecting and analyzing secondary data such as laws, regulations, arbitration decisions and related literature. The research results show that the default dispute resolution process through BANI involves several steps, including arbitration selection, trial process, and final decision. The advantages of resolving default disputes through BANI include speed, legal certainty through arbitration awards, and the diversity of arbitrators who can provide different points of view in resolving disputes. Based on research findings, the decision of the Denpasar District Court Class I A Number 3/Pdt.G/2017/PN.Dps is based on Article 3 of Law no. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. The judge stated that the District Court did not have the authority to decide disputes between two parties who were bound by an arbitration agreement. This shows that if a dispute occurs, the parties must resolve it through deliberation. If deliberations are unsuccessful, the resolution will be handed over to the Indonesian National Arbitration Board (BANI).